Plant cell proliferation inside an inorganic host - Perullini, Ana Mercedes (2007)
In recent years, much attention has been paid to plant cell culture as a tool for the production of secondary metabolites and the expression of recombinant proteins. Plant cell immobilization offers many advantages for biotechnological processes. However, the most extended matrices employed, such as calcium-alginate, cannot fully protect entrapped cells. Sol-gel chemistry of silicates has emerged as an outstanding strategy to obtain biomaterials in which living cells are truly protected. This field of research is rapidly developing and a large number of bacteria and yeast-entrapping ceramics have already been designed for different applications. But even mild thermal and chemical conditions employed in sol-gel synthesis may result harmful to cells of higher organisms. Here we present a method for the immobilization of plant cells that allows cell growth at cavities created inside a silica matrix. Plant cell proliferation was monitored for a 6-month period, at the end of which plant calli of more than 1 mm in diameter were observed inside the inorganic host. The resulting hybrid device had good mechanical stability and proved to be an effective barrier against biological contamination, suggesting that it could be employed for long-term plant cell entrapment applications.